A scalable and secure RFID mutual authentication protocol using ECC for Internet of Things. (16th January 2019) - Naeem, Muhammad; Chaudhry, Shehzad Ashraf; Mahmood, Khalid; Karuppiah, Marimuthu; Kumari, Saru
Summary: Very recently, Alamr et al (J. Supercomput 1‐14 doi: 10.1007/s11227‐016‐1861‐1) presented a radio frequency identifier (RFID) authentication protocol for the Internet of Things (IoT) through elliptic curve cryptography (ECC). They claimed the protocol to achieve several security properties and thwart all known attacks. However, this paper shows that their scheme is having correctness and scalability issues. The reader in their protocol can accommodate only one tag, which is not desirable in the IoT environments. The paper finally suggests an improvement to cater the correctness and scalability issues. Abstract : Very recently, Alamr et al presented an RFID authentication protocol for Internet of Things (IoT) through elliptic curve cryptography (ECC). They claimed the protocol to achieve several security properties and thwarts all known attacks. However, this paper shows that their scheme is having correctness and scalability issues. The paper finally, suggests an improvement to cater the correctness and scalability issues.